Source studies of the madrasahs education system of the Ashtarkhanid period (XVII-XVIII centuries) (Eurasian Journal of History, Geography and Economics, 2023)
In the history of our country, during the period of more than 150 years (1601-1757), many buildings such as mosques and madrasahs, bazaars, houses, caravanserais were built at the expense of rulers, palace officials, rich people and scholars. An architectural monument built in Bukhara by the Ashtarkhani ruler Abdulaziz Khan (1614-1681) - Abdulaziz Khan madrasah was built in 1652 by the architects Muhamad Salih, the painterhusnikhatcher Mavlano bini Khoja Muhammad Amin, and the potter-sealer Haji Babas on the south side of the Ulugbek madrasah. They built the madrasah with a large porch, a two-story gallery, a wide courtyard, four porches, two porches, a summer and winter mosque, a large classroom, and they made flower bouquets at the four corners. The structure of the madrasah is simple and the rooms have two floors. Between each side of the Chorsi courtyard is a covered porch. The porch is decorated with various patterns, muqarnas and pendants. The following article contains valuable information about the source studies of the educational system of madrasahs in the XVII-XVIII centuries